Approaching the socialist factory and its workforce: considerations from fieldwork in (former) Yugoslavia. (1st January 2017) - Archer, Rory; Musić, Goran
Abstract: The socialist factory, as the 'incubator' of the new socialist (wo)man, is a productive entry point for the study of socialist modernization and its contradictions. By outlining some theoretical and methodological insights gathered through field-research in factories in former Yugoslavia, we seek to connect the state of labour history in the Balkans to recent breakthroughs made by labour historians of other socialist countries. The first part of this article sketches some of the specificities of the Yugoslav self-managed factory and its heterogeneous workforce. It presents the ambiguous relationship between workers and the factory and demonstrates the variety of life trajectories for workers in Yugoslav state-socialism (from model communists to alienated workers). The second part engages with the available sources for conducting research inside and outside the factory advocating an approach which combines factory and local archives, print media and oral history.